2017
DOI: 10.1080/10641963.2017.1291659
|View full text |Cite
|
Sign up to set email alerts
|

Association of ACE gene A2350G and I/D polymorphisms with essential hypertension in the northernmost province of China

Abstract: Angiotensin converting enzyme (ACE) gene, as a strong candidate gene for essential hypertension(EH), has been extensively studied. In this study, we carried out a population-based case-control study to explore whether ACE gene I/D and A2350G polymorphisms could consider to be risk factors for EH. A total of 2040 subjeces were recruited from Chinese Han in this study, out of which 1010 were cases and 1030 were normotensive individuals. ACE gene A2350G and I/D polymorphisms were amplified by polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…In contrast to Caucasian populations, there are a limited number of studies in Asian populations on the relationship of the ACE polymorphisms and hypertension. While there are associations between ACE I/D and hypertension in some Chinese [30, 31] and Indian [32, 33] populations, lack of such associations has also been reported [34, 35]. Other genes in the RAAS including AGT, AGTR1, and CYP11B2 have also been widely studied [36].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Caucasian populations, there are a limited number of studies in Asian populations on the relationship of the ACE polymorphisms and hypertension. While there are associations between ACE I/D and hypertension in some Chinese [30, 31] and Indian [32, 33] populations, lack of such associations has also been reported [34, 35]. Other genes in the RAAS including AGT, AGTR1, and CYP11B2 have also been widely studied [36].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed description of the procedure of ACE gene D/I genotype identification has been described previously (Comey et al, 1994;Sun et al, 2018;He et al, 2019). DNA samples were extracted from buccal mucosal cells by cotton swabs.…”
Section: Ace Gene D/i Polymorphism Identification and Classificationmentioning
confidence: 99%
“…A number of studies have also found a high frequency of metabolic syndrome in ID carriers. (17)(18)(19)(20) Thus, the ACE I/D polymorphism was found to be associated with metabolic risk factors in indigenous EH patients of the North of Yakutia.…”
Section: Resultsmentioning
confidence: 99%